HUBUNGAN TINGKAT KEPATUHAN BEROBAT TERHADAP KENDALI GLUKOSA DARAH PASIEN DIABETES MELITUS TIPE 2 DI RUMAH SAKIT DIRGAHAYU SAMARINDA - Ardila, Rindi; Victoria Yulita (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2025)
Type 2 diabetes mellitus is a chronic metabolic disease characterized by high blood glucose levels, with incidence rates continuing to rise worldwide, including in Samarinda City, which has the highest prevalence in East Kalimantan (3.04%). Patient adherence to drug therapy is an important factor in achieving successful blood glucose control and preventing complications. This study aimed to assess the level of adherence of outpatients with type 2 diabetes mellitus at Dirgahayu Samarinda Hospital to the use of antidiabetic drugs. This was a prospective study with a cross-sectional design involving 50 respondents with type 2 diabetes mellitus. Data were collected through the MMAS-8 adherence questionnaire and review of patient medical records. Data analysis was performed using statistical software with frequency distribution analysis and chi-square tests. The results showed that 23 respondents (46%) had high compliance, 17 respondents (34%) showed moderate compliance, and 10 respondents (20%) were in the low compliance category. No significant relationship was found between the level of compliance and blood glucose control (p = 0.249 > ? = 0.005). In conclusion, the level of patient compliance with treatment is not the only factor determining success in controlling blood glucose levels, as there are various other aspects that also play a role in influencing the stability of these glucose levels.